(untitled) (Revista Internacional de Folkcomunicação, 2020)
We present a reflection on the use of contemporary communication tools by the rural population. To this end, we did a bibliographic review about the conceptions of rural communication, bringing some problematizations for its updating. Then, taking YouTube as a parameter, we talk too about the release of the emitting pole and the democratization of speech. For this, our empirical object was the channel “Humorista da Serraria Ofc”, starring farmers from the Serraria sítio, from the city of João Dias, Rio Grande do Norte. We understand that there is a movement that promotes the updating of the concept of rural communication, bearing in mind that the protagonism of this field comes from rural communities. They are increasingly using digital platforms to share information and stories that permeate life in the countryside. Rural communication; YouTube; Serraria Ofc humorist; Media activism; Content production.